Study on the micro-crack evolution of concrete subjected to stress corrosion and magnesium sulfate. (15th June 2017) - Tan, Yongshan; Yu, Hongfa; Ma, Haiyan; Zhang, Yunqing; Wu, Chengyou
Highlights: The damage behaviors of concrete under the combined actions of MgSO4 attack and flexural or tensile loads were studied. A crack density model was proposed to evaluate the damage degree of the concrete. The deterioration mechanisms of two types of concrete under various corrosion conditions were analyzed. Abstract: The deterioration processes of two types of concrete under chemical corrosion (MgSO4 ), tensile loading coupled with chemical corrosion or flexural loading coupled with chemical corrosion were investigated in this study. Tensile stress and flexural stress loading devices that were designed by the authors were used. A relative dynamic elastic modulus test using the ultrasonic method was utilized, and through the derivation of empirical equations, a crack density model was obtained to describe the concrete damage process. Furthermore, scanning electron microscopy (SEM) was used to investigate the microstructure changes inside the concrete. The results indicated that the flexural and tensile loads significantly affected the deterioration of concrete when combined with magnesium sulfate. Exposure to magnesium sulfate coupled with tensile loading is a harsh environment for concrete. The rate of concrete deterioration under different stress conditions at the same loading level is ranked as follows: tensile stress coupled with chemical corrosion > flexural stress coupled with chemical corrosion > chemical corrosion.